2013
DOI: 10.1007/s10147-012-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variables for predicting metastatic renal cell carcinoma patients who might not benefit from cytoreductive nephrectomy: neutrophil-to-lymphocyte ratio and performance status

Abstract: Preoperative NLR elevation is significantly associated with poor outcomes in patients with metastatic RCC who underwent CN. Patients with NLR ≥4.0 and ECOG-PS ≥ 1 might not benefit from immediate CN after initial diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
4
38
1
2
Order By: Relevance
“…In contrast to recently published articles, our univariate analysis did not demonstrate the independent prognostic value of NLR; [13][14][15][16][17][18] perhaps this is because only 24% of our study population had an elevated NLR. This finding should be confirmed with a much larger cohort of patients.…”
Section: Knowledge Itcontrasting
confidence: 55%
“…In contrast to recently published articles, our univariate analysis did not demonstrate the independent prognostic value of NLR; [13][14][15][16][17][18] perhaps this is because only 24% of our study population had an elevated NLR. This finding should be confirmed with a much larger cohort of patients.…”
Section: Knowledge Itcontrasting
confidence: 55%
“…Further retrospective data showed than CN was [25]. Together, these retrospective data suggest that CN might have a role in some well-selected individuals [26]. In the present study, we demonstrated that only patients with ECOG score of 0 to 1 or good/intermediate MSKCC prognostic score had a benefit from CN.…”
Section: Discussionmentioning
confidence: 56%
“…Some of these factors, such as performance status [23] , haemoglobin levels [24] , LDH and albumin [25,26] have also shown to have a predictive value of survival in patients who underwent CN for mRCC in other studies. An interesting study from Rausch et al [27] showed that CRP levels could also be helpful in selecting mRCC patients likely to benefit from metastasectomy.…”
Section: Discussionmentioning
confidence: 99%